The biochemistry surrounding bovine conceptus elongation. Issue 2 (10th June 2019) - Simintiras, Constantine A; Sánchez, José M; McDonald, Michael; Lonergan, Patrick
Abstract: Conceptus elongation is a fundamental developmental event coinciding with a period of significant pregnancy loss in cattle. The process has yet to be recapitulated in vitro, whereas in vivo it is directly driven by uterine secretions and indirectly influenced by systemic progesterone. To better understand the environment facilitating this critical reproductive phenomenon, we interrogated the biochemical composition of uterine luminal fluid from heifers with high vs physiological circulating progesterone on days 12–14 of the estrous cycle—the window of conceptus elongation-initiation—by high-throughput untargeted ultrahigh-performance liquid chromatography tandem mass spectroscopy. A total of 233 biochemicals were identified, clustering within 8 superpathways [amino acids (33.9%), lipids (32.2%), carbohydrates (8.6%), nucleotides (8.2%), xenobiotics (6.4%), cofactors and vitamins (5.2%), energy substrates (4.7%), and peptides (0.9%)] and spanning 66 metabolic subpathways. Lipids dominated total progesterone (39.1%) and day (57.1%) effects; however, amino acids (48.5%) and nucleotides (14.8%) accounted for most day by progesterone interactions. Corresponding pathways over-represented in response to day and progesterone include (i) methionine, cysteine, s-adenosylmethionine, and taurine (9.3%); (ii) phospholipid (7.4%); and (iii) (hypo)xanthine and inosine purine metabolism (5.6%). Moreover, under physiological conditions, the uterine lumen undergoes a metabolic shift after day 12, and progesterone supplementation increases total uterine luminal biochemical abundance at a linear rate of 0.41-fold day −1 –resulting in a difference ( P  ≤ 0.0001) by day 14. This global metabolic analysis of uterine fluid during the initiation of conceptus elongation offers new insights into the biochemistry of maternal–embryo communication, with implications for improving ruminant fertility. Abstract : High systemic progesterone alters bovine uterine luminal fluid biochemistry during the conceptus elongation-initiation window.